♣Evaluation of clinicopathological profiles and development of a risk model in renal epithelioid angiomyolipoma patients: a large-scale retrospective cohort study - Aihetaimujiang Anwaier; Wen-Hao Xu; Xi Tian; Tao Ding; Jia-Qi Su; Yue Wang; Yuan-Yuan Qu; Hai-Liang Zhang; Ding-Wei Ye (BMC Urology, 2022)
Abstract Background To identify the malignant potential and prognostic indicators of renal epithelioid angiomyolipoma (eAML), clinicopathological and molecular features as well as the drug efficacy of 67 eAML cases were analyzed. Materials and methods Sixty-seven renal eAML patients were enrolled and the immunohistochemical features of these patients were examined. FFPE slides of all patients were re-examined. 21 patients with metastasis received Everolimus 10 mg orally once daily. Responses were evaluated with RECIST criteria by three authors. A risk stratification model was constructed using the following factors: pT3 and pT4, presence of necrosis, mitotic count ≥ 2; the presence of atypical mitoses; severe nuclear atypia, SMA negative, Ki-67 ≥ 10%. Results The average percentage of the epithelioid component was 85.6% (range 80–95%). Immunohistochemically, Ki-67 ≥ 10% and negative SMA staining were significantly correlated with malignant characteristics (Ki-67: p < 0.001; SMA: p = 0.001). Survival analysis suggested that pT3-pT4 stage, presence of necrosis, severe nuclear atypia, presence of atypical mitoses, mitotic count ≥ 2, Ki-67 ≥ 10% and negative SMA expression were significantly associated with poorer PFS and OS (p < 0.05). The risk model sufficiently discriminated recurrence/metastasis (AUC = 0.897) and cancer-specific mortality (AUC = 0.932) of renal eAML patients in different risk groups. 21 patients had received Everolimus targeted therapy after recurrence/metastasis. The best response for Everolimus treatment was 8/21 (38.1%) partial responses (PR), 9/21 (42.9%) stable disease (SD) and 4/21 (19.0%) progressive disease (PD). Conclusion The risk stratification model could well distinguish eAML patients at high risk of recurrence/metastasis. Everolimus targeted treatment showed good efficacy in patients with recurrence/metastasis.